2011
DOI: 10.1645/ge-2469.1
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Protein Capable of Binding To Fatty Acids and Bile Salts in Giardia lamblia

Abstract: A specific fatty acid binding protein was isolated from Giardia lamblia, using an affinity column with butyric acid acting as a ligand in place of stearic acid. This method has proved to be more efficient than the one previously described using stearic acid as ligand. The purified fraction showed 8 electrophoretic bands of proteins, with molecular weights ranging between 8 and 80 kDa. This pattern is a consequence of the aggregation of a protein with a molecular weight of 8,215 Da, corresponding to the lower m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The authors suggested that intracellular bile salts may facilitate lipid trafficking and membrane biosynthesis in Giardia . Indeed, Giardia lipid-binding proteins have been shown to have higher affinity for bile salts than fatty acids, suggesting that lipids are incorporated by these binding proteins more readily inside the micelles formed by bile salts than by free fatty acids (de la Guardia et al, 2011 ). Studies also suggest that conjugated bile salts have a role in promoting Giardia encystation (Gillin, 1987 ; Gillin et al, 1989 ), a vital step in the parasite life cycle that enables parasite survival outside of its host.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that intracellular bile salts may facilitate lipid trafficking and membrane biosynthesis in Giardia . Indeed, Giardia lipid-binding proteins have been shown to have higher affinity for bile salts than fatty acids, suggesting that lipids are incorporated by these binding proteins more readily inside the micelles formed by bile salts than by free fatty acids (de la Guardia et al, 2011 ). Studies also suggest that conjugated bile salts have a role in promoting Giardia encystation (Gillin, 1987 ; Gillin et al, 1989 ), a vital step in the parasite life cycle that enables parasite survival outside of its host.…”
Section: Discussionmentioning
confidence: 99%
“…It is increasingly recognized that, within the luminal ecology of the human intestine, resident microbiota modify ingested nutrients and their metabolites, influencing nutrient availability and uptake. Giardia lacks fundamental enzymes necessary for generating critical biomolecules such as cholesterol and therefore must rely on acquisition of these materials from the luminal environment [ 110 112 ]. The parasite acquires nutrients primarily via bulk-phase uptake in endocytic vacuoles localized to the exposed dorsal (non-adherent) side [ 113 ], adheres to epithelial cells using the ventral disc [ 114 , 115 ], and may direct fluid flow toward adherent parasites via coordinated flagellar motion [ 116 ].…”
Section: Determining How Giardia Causes Diseasementioning
confidence: 99%
“…Some reported cases of giardiasis were among homosexual men, immunocompetent and immunocompromised patients. In addition, giardiasis in children living in developing countries can cause growth retardation (de la Guardia et al, 2011). The main aim of this study is to evaluate the pathogenicity of G. duodenalis infection through the histopathological examination of the experimentally immunosuppressed animal model.…”
Section: Introductionmentioning
confidence: 99%